A Novel Approach for Diagnosing Neuro-Developmental Disorders using Artificial Intelligence - Priyanka Vashisht; Aman Jatain (Inteligencia Artificial, 2023)
Artificial Intelligence (AI) has been rapidly advancing especially in the field of medicine. One of the highly considerable medical fields in the world today is that of neurodevelopment and diagnosing any disorders pertaining to the same can be overwhelming. Considering the fact that neurodevelopment plays a significant role in the growth and nourishment of a child, the former sentence is an irony as parents wouldn’t wish for their children to possess reduced capabilities in comparison to other children of the same age. In fact, testing the metal growth of a child is a tedious task which involves visiting the doctor each time and spending a lot of time. The proposition of this paper overcomes the above--mentioned hassles by utilizing computer aided techniques for identifying neurodevelopmental disorder. The proposed framework has its foundation over mathematical and Deep Learning (DL) models which helps in the diagnosis of four varied neurodevelopmental disorders which often tend to occur in the early phases of a child’s life. The application put forward here would suggest suitable remedies and strategies to parents and teachers which they can adopt to help their child recover from the illness.